2015
DOI: 10.1093/femsyr/fov012
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous tyrosol inhibits planktonic cells and biofilms of Candida species and enhances their susceptibility to antifungals

Abstract: Tyrosol is a quorum-sensing molecule of Candida albicans able to induce hyphal development in the early and intermediate stages of biofilm growth. In the present study, we evaluated the effect of high concentrations of exogenous tyrosol on planktonic cells and biofilms of C. albicans (n = 10) and C. tropicalis (n = 10), and investigated whether tyrosol could be synergic to antifungals that target cellular ergosterol. Antifungal susceptibility and drug interaction against planktonic cells were investigated by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 42 publications
4
52
0
1
Order By: Relevance
“…Cordeiro et al . () showed that exogenous tyrosol in supraphysiological concentration (2·5–5 mmol l −1 ) significantly inhibits the growth of planktonic C. albicans and C. tropicalis isolates. Present study has found no inhibitory effect of tyrosol against C. parapsilosis planktonic cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cordeiro et al . () showed that exogenous tyrosol in supraphysiological concentration (2·5–5 mmol l −1 ) significantly inhibits the growth of planktonic C. albicans and C. tropicalis isolates. Present study has found no inhibitory effect of tyrosol against C. parapsilosis planktonic cells.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Cordeiro et al . () reported synergistic interactions of tyrosol with amphotericin B and azoles against C. albicans and C. tropicalis planktonic cells based on FICI determination. Unlike these findings, current study using tyrosol combined with caspofungin or micafungin against C. parapsilosis planktonic cells has not found synergistic interactions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of these molecules to disrupt yeast biofilms is currently being studied in the clinical field (Wongsuk et al 2016). Additionally, the combination of antifungals with QS molecules has been studied especially against Candida albicans biofilms (Shanmughapriya et al 2014;de Cordeiro et al 2015;Katragkou et al 2015;Boz o et al 2016;Kov acs et al 2016). To the best of our knowledge, there is no information available about the effectivity of combinatory treatments against yeast biofilms inhabiting food and food processing devices.…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to speculate that a similar mechanism contributes to the action of p -cresol. Notably, several other phenolic compounds have been reported to positively or negatively affect Candida viability, morphology, and biofilm formation; these include but are not limited to tyrosol (67, 68), p -coumaric acid (69), ferulic acid (70), caffeic acid (71), boric acid (72), and eugenol (73). These observations, together with the identification of more-complex inhibitors (74, 75), may lead to the identification of general structural principles of compounds that govern Candida proliferation and the yeast-to-hypha transition.…”
Section: Discussionmentioning
confidence: 99%